2021
DOI: 10.3389/fmicb.2021.658421
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of Deoxynivalenol by Nocardioides sp. ZHH-013: 3-keto-Deoxynivalenol and 3-epi-Deoxynivalenol as Intermediate Products

Abstract: Deoxynivalenol (DON) is one of the most devastating and notorious contaminants in food and animal feed worldwide. A novel DON-degrading strain, Nocardioides sp. ZHH-013, which exhibited complete mineralization of DON, was isolated from soil samples. The intermediate products of DON generated by this strain were identified by high-performance liquid chromatography and ultra-performance liquid chromatography tandem mass spectrometry analyses. It was shown that, on an experimental level, 3-keto-DON was a necessar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…Among the bacteria of the genus Nocardioides , there are also psychrophilic representatives isolated from cold habitats; for the species Nocardioides oleivorans , growth on oil was shown [ 61 , 62 ]. Members of the genus Mycobacterium are also known degraders of various aromatic hydrocarbons, which was confirmed by discovery of the relevant genes [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among the bacteria of the genus Nocardioides , there are also psychrophilic representatives isolated from cold habitats; for the species Nocardioides oleivorans , growth on oil was shown [ 61 , 62 ]. Members of the genus Mycobacterium are also known degraders of various aromatic hydrocarbons, which was confirmed by discovery of the relevant genes [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…Zhang, et al. (2021) screened a novel DON‐degrading strain, Nocardioides sp. ZHH‐013 from the soil, which can degrade DON (168.74 μmol/L) to 3‐keto‐DON and 3‐epi‐DON, achieving DON mineralization.…”
Section: Don Biological Detoxification Methods and Nutritional Mitiga...mentioning
confidence: 99%
“…Recently Zhang et al (2021) reported a novel strain, Nocardioides sp. ZHH-013, isolated from soil and able to transform DON (168.74 μM) into 3-epi-DON with 80% efficiency within 48 h of incubation at 30 °C [ 123 ]. The ultraperformance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) and HPLC study of DON metabolites showed that DON was catabolized in a two-step mode with a formation of 3-keto-DON followed by its conversion into 3-epi-DON, which further disappeared.…”
Section: Biotransformation Of Deoxynivalenolmentioning
confidence: 99%